Italian Tsunami Effects Database (ITED): The First Database of Tsunami Effects Observed Along the Italian Coasts - Alessandra Maramai (Frontiers in Earth Science, 2021)
Traditional tsunami catalogues are conceived as a collection of tsunamis classified by the generating cause, providing a general description of the effects observed for each tsunami. Those catalogues, even if they provide fundamental information, are not suitable for producing an exhaustive picture of the geographical distribution of the tsunami effects. In this paper we introduce the new Italian Tsunami Effects Database (ITED), a collection of evidence documenting the effects along the Italian coasts from historical times to present. The database comes forth the Euro-Mediterranean Tsunami Catalogue (EMTC) and focusses on the effects of tsunamis observed along the Italian coasts providing descriptive and quantitative information for each OP. The information reported in ITED does not only concern the effects produced by Italian tsunamis, but also those effects produced by tsunamis originated outside the Italian territory. ITED contains 318 OPs, related to 73 Italian tsunamis and to four tsunamis which occurred outside Italy. The database can be accessed through a WebApp that displays for each OP the description of effects, quantitative data (run-up, inundation, withdrawal, etc.) and tsunami intensity with the corresponding bibliographic references. The database also provides the tsunami intensity distribution along time (tsunami-history) for each site, allowing the end user to know how a place has been affected by tsunamis over the time. The information contained in ITED makes this database a useful tool to understand how tsunamis have affected the Italian territory and emphasizes the importance of studying the tsunami hazard along the Italian coasts.